The C-reactive protein (CRP)-albumin-lymphocyte (CALLY) index exhibits an L-shaped association with all-cause mortality in rheumatoid arthritis patients: a retrospective cohort study - Jialin Zhang; Yanhua Lin; Jingyan Zeng; Guihu Luo; Pan Liao; Qianyun Chen; Han Zhong; Simei Liang; Cailiu Zhou; Bin Yang; Xing Li (BMC Rheumatology)
Abstract Background The C-reactive protein (CRP)-albumin-lymphocyte (CALLY) index is a novel biomarker reflecting inflammation, nutrition, and immune status, and its potential clinical significance and prognostic role in patients with rheumatoid arthritis (RA) has not been reported. Aim The objective of this study was to investigate whether CALLY is associated with all-cause mortality in RA patients. Methods The characteristics of 1101 RA patients and 18,047 non-RA individuals were collected from the National Health and Nutrition Examination Survey (NHANES) database between 1999 and 2010. The CALLY index is calculated as albumin × lymphocyte count / (CRP × 10). Multivariable Cox regression models were used to assess the association between the CALLY index and all-cause mortality in RA patients. Restricted cubic spline (RCS) analysis was applied to evaluate potential linear or nonlinear relationships between the CALLY index and mortality. Kaplan-Meier survival curves were used to assess survival probabilities across different CALLY levels in RA patients.The final analysis was conducted on July 10, 2024. Results Multivariable logistic regression analysis indicated that a low CALLY index was significantly associated with RA patients when compared to non-RA individuals, with an odds ratio (OR) of 0.74 (95% CI: 0.65–0.83). Cox regression models revealed that RA patients with a higher CALLY index showed a decreased risk of all-cause mortality, with a hazard ratio (HR) of 0.62 (95% CI: 0.51–0.77). RCS analysis demonstrated a L-shaped relationship between the CALLY index and survival outcomes of RA patients. Segmented regression identified an optimal cutoff value for the CALLY index at 12.79, where values below this threshold were inversely correlated with all-cause mortality risk. Subgroup analysis suggested a synergistic interaction between a high Log-CALLY index, male, and age below 60 years. Kaplan-Meier survival curve analysis showed significantly higher survival rates in the high CALLY group compared to the low CALLY group (P = 0.0012). Conclusions The CALLY index is a valuable biomarker for evaluating the prognosis of patients with RA, and a lower CALLY index indicates an increased long-term mortality risk in RA patients, which suggests the importance of comprehensive assessment for inflammatory status and immune function. Clinical trial number Not applicable.